2002
DOI: 10.1177/0272431602022002004
|View full text |Cite
|
Sign up to set email alerts
|

Racial Socialization Messages and the Quality of Mother/Child Interactions in African American Families

Abstract: Racial socialization messages were examined within a particular ecological niche: two-parent, African American families with a child in early adolescence. The linkage between mothers'provision of racial socialization messages and family process components (e.g., communication, warmth, negativity, child monitoring, and involvement) of the mother/child relationship was examined. Sixty-six African American mothers and their early adolescent sons and daughters participated in videotaped mother/child interactions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
95
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 21 publications
5
95
0
Order By: Relevance
“…The presence of a low or high belief in racial socialization messages did not evidence a strong influence on child mental health service use. These findings are similar to those of Frabutt et al (2002) who found that parents who expressed more moderate levels of racial socialization messages were most likely to evidence the highest levels of parent-child communication, child monitoring, child involvement, and lowest levels of negativity. Although this is the sole pre-existing study that examines the effect of parent racial socialization messages at low, moderate, and high levels, it is interesting that the findings indicate the same type of curvilinear relationship between parental endorsement of racial socialization parenting practices and outcomes.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The presence of a low or high belief in racial socialization messages did not evidence a strong influence on child mental health service use. These findings are similar to those of Frabutt et al (2002) who found that parents who expressed more moderate levels of racial socialization messages were most likely to evidence the highest levels of parent-child communication, child monitoring, child involvement, and lowest levels of negativity. Although this is the sole pre-existing study that examines the effect of parent racial socialization messages at low, moderate, and high levels, it is interesting that the findings indicate the same type of curvilinear relationship between parental endorsement of racial socialization parenting practices and outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…The specific findings of Frabutt et al (2002) also have implications in the current study, particularly in reference to the parents in the moderate spiritual or religious coping and extended family caring racial socialization groups who were most likely to have used child mental health services. More specifically, the authors linked moderate levels of parental belief in racial socialization to stronger family processes.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations